2013
DOI: 10.1002/chem.201204596
|View full text |Cite
|
Sign up to set email alerts
|

The “Click” Reaction Involving Metal Azides, Metal Alkynes, or Both: An Exploration into Multimetal Structures

Abstract: CuI‐catalyzed 1,3‐cycloaddition of azides and alkynes (CuAAC) is one of the most powerful synthetic methodologies known. However, its use to prepare well‐defined multimetallic structures is underdeveloped. Apart from the applications of this reaction to anchor different organometallic reagents to surfaces, polymers, and dendrimers, only isolated examples of CuAAC with metal–η1‐alkyne and metal–azide complexes to prepare multimetal entities have been reported. This concept sketches the potential of these reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…An X‐ray crystal structure of this complex is shown in Figure 2 (Table 3, see below) and reveals that the C s ‐symmetric triazolato ligand is bound to the metal center by N2, which implies that an N1→N2 linkage isomerization occurs in the course of the cycloaddition reaction. This type of linkage isomerization has been reported numerous times for 1,3‐dipolar cycloadditions with metal‐coordinated azides 4462…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…An X‐ray crystal structure of this complex is shown in Figure 2 (Table 3, see below) and reveals that the C s ‐symmetric triazolato ligand is bound to the metal center by N2, which implies that an N1→N2 linkage isomerization occurs in the course of the cycloaddition reaction. This type of linkage isomerization has been reported numerous times for 1,3‐dipolar cycloadditions with metal‐coordinated azides 4462…”
Section: Resultssupporting
confidence: 60%
“…This type of linkage isomerization has been reported numerous times for 1,3-dipolar cycloadditions with metal-coordinated azides. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Attempted cycloadditions of ruthenium(II)-azido complex 1 with non-activated alkynes: Although the cycloaddition with DMAD proceeded rapidly, DMAD and related propargylic esters are excellent Michael acceptors and hence they react with cellular thiols, causing glutathione depletion and protein cross-linking. Accordingly, such compounds are cytotoxic and thus unsuitable for biological applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Others [5][6][7] extended iClick to include the already prevalent [8][9] cycloaddition of an organic substrate to either a metal-azide or metal-acetylide. 7,[10][11][12][13][14][15][16][17][18][19][20][21] Important to this work, Gray et al 22 demonstrated that gold-acetylides and gold-azides will undergo cycloaddition to their organic counterparts. Despite the fact that several transition metals other than Cu(I) catalyze the azide-alkyne cycloaddition, including ruthenium, silver, and iridium, [23][24][25][26] it became apparent that not all metal-acetylide/azide species will participate in the iClick cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Critical in the pursuit of building complexity is the precise control of bond forming events and is particularly exemplified by the Cu I catalyzed azide-alkyne cycloaddition reaction (CuAAC). Others [11][12][13] have broadened the iClick concept to include the cycloaddition of organic substrates to either a metal-azide or metal-acetylide (M; Scheme 1), which are already rather prevalent reactions, [13][14][15][16][17][18][19][20][21][22][23][24][25] and the subject of reviews. The metal-azide/metal-acetylide cycloaddition (M-M′) was given the term inorganic click (iClick) as a distinguishing feature that calls attention to chemistry occurring within the coordination sphere of a metal ion.…”
Section: Introductionmentioning
confidence: 99%